Parasitic infestations in children in a metropolis - T. M. Chernova; D. O. Ivanov; O. I. Veduta; V. N. Timchenko; E. V. Barakina; E. B. Pavlova; I. Yu. Bazunova; A. A. Zherebtsova (LLC "Diagnostics and Vaccines", 2024)
Even when asymptomatic, intestinal parasitosis can have a significant impact on the health of children. Materials and methods. An analysis of the medical documentation of the children's clinic for 2016-2023 was carried out. Results. It has been established that enterobiasis dominates in children living in St. Petersburg (87.8%-98.8%), the proportion of ascariasis and giardiasis in different years did not exceed 5.2% and 10.0%, respectively. The maximum proportion of those affected by E. vermicularis (50.6%-66.8%) and Giardia (67.3%) was in the age group of 7-14 years, while ascariasis most often affected children 3-6 years old (51.7%). Enterobiasis was more often recorded during annual preventive examinations (September-November) (52.0%-65.9%), ascariasis was detected at a later date - November-January (41.5%), the largest number of episodes of giardiasis was observed in the spring months (53.9%). If helminthic infestations in all cases were asymptomatic and were discovered by chance during a microscopic examination of feces, then in the case of giardiasis, 46.2% of those infected complained of abdominal pain (42.3%), discomfort after eating (25.0%), diarrhea/constipation (21.2%), bloating (19.2%), frequent belching of air (13.5%). Thus, a single microscopic examination of feces is not very informative. Knowledge of the clinical and epidemiological features of parasitic infestations will allow the pediatrician to conduct an in-depth examination of the child to decide on antiparasitic treatment